RABIES OUTBREAK IN DOMPU, WEST NUSA TENGGARA, INDONESIA: A CASE STUDY - Rahmad Rahmad; Mira Fatmawati; Nugroho Nurponco Priyanto; Ninik Djajati; Mujahidin Mujahidin; Zainal Arifin; Iris Juita Kastianti; Sri Andarini; Harun Al Rasyid; Lilik Zuhriyah (Universitas Brawijaya, 2021)
Rabies, transmitted through a bite from a dog, is a highly fatal disease that is a health hazard throughout the world including Indonesia. In February 2019, there was an outbreak of rabies at Dompu, West Nusa Tenggara (WNT), Indonesia. As such, Dompu district has become one of the beginning points for many rabies cases being experienced in WNT. Lately, there have been fatal cases of the outbreak to the tune of 1,315 victims due to rabies-borne animal bite. Among these cases, nine of them are human rabies. Out of the 182 samples examined for brain rabid animal, 90 turned positive. Efforts from local, provincial, and federal agencies representatives activated a rabies response involving update of policies, enhancing of surveillance, a campaign to educate the public as well as widespread vaccination of domestic and wild animals. There has not been experienced a rabies outbreak like this in WNT region, Indonesia, over the years. Therefore, there require integration of all intervention strategies as well as a collaboration of all human health, animal health, and wildlife authority to bring to a halt the outbreak. To further enhance the intervention strategies, the government is recommended to respond immediately.